Improvement in dielectric, ferroelectric and ferromagnetic characteristics of Ba0.9Sr0.1Zr0.1Ti0.9O3-NiFe2O4 composites. Issue 13 (September 2017) - Jain, Aditya; Panwar, Amrish K.; Jha, A.K.; Sharma, Yogesh
Abstract: Multiferroic composites with the composition (1- x )Ba0.9 Sr0.1 Zr0.1 Ti0.9 O3 -( x )NiFe2 O4 ( x =0.0, 0.05, 0.10, 0.20 and 0.30) were prepared by mechano-chemical activation technique. Rietveld refined X-ray diffraction pattern shows the formation of individual perovskite (BSZT) and inverse spinel (NFO) phases for all the four composite samples. Microstructural investigation reveals that the inhomogeneity in grains increases with addition of NFO as compared to bare BSZT sample. Dielectric studies show that all the samples exhibit a well-defined ferroelectric to paraelectric transition peak. Further, the diffuseness of the samples increases as NFO content increases. Ferroelectric properties were found to be superior for (1- x )BSZT-( x )NFO sample with x =0.05 and decreases on further increase in NFO content. Dielectric breakdown strength also shows the similar trend as ferroelectricity and shows a maximum for x =0.05 ferrite (NFO) fraction. Magnetic measurement of BSZT-NFO composite samples shows a gradual increase in saturation magnetization and coercive field ( H c ) with increasing NFO content. Graphical abstract: